Impacts of the Québec carbon emissions trading scheme on plant-level performance and employment. Issue 3 (4th May 2019) - Hanoteau, Julien; Talbot, David
Abstract: In 2013, Québec implemented a greenhouse gas (GHG) emissions trading system (QC ETS), despite opposition from industry, which feared loss of competitiveness and warned about job destruction. This article assesses the impact of that carbon regulation on industrial facilities in Québec. Conditional difference-in-differences ordinary least squares regressions show that regulated plants reduced their GHG emissions by about 9.8%, employment by about 6.8% and carbon intensity by about 3.7% more compared to non-regulated plants in the rest of Canada during the period 2013–2015. This suggests that facilities adapted to the new program by improving their technology, but first and foremost by scaling down their activity, which raises questions about the ability of the QC ETS to induce enough environmental investment and innovation in industrial facilities. The results, in terms of employment effects, contrast with the findings of similar studies on the early stages of the European ETS and the British Columbia carbon tax scheme, and this information challenges the initial allocation scheme for permits, in particular, with a view to a green fiscal reform.